2005
DOI: 10.1016/j.worlddev.2005.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Why Is Child Malnutrition Lower in Urban Than in Rural Areas? Evidence from 36 Developing Countries

Abstract: hile ample evidence documents that urban children generally have better nutritional status than their rural counterparts, recent research suggests that urban malnutrition is on the rise. The environment, choices, and opportunities of urbanites differ greatly from those of rural dwellers-from employment conditions to social and family networks to access to health care and other services. Given these differences, understanding the relative importance of the various determinants of child malnutrition in urban and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

40
276
6
12

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(334 citation statements)
references
References 11 publications
40
276
6
12
Order By: Relevance
“…On the other hand some rural health areas like Akok Maka and Mindourou showed very low or no case of malnutrition for the time duration of the study. The result of this study in terms of geographical distribution is in contrary to the research of Smith et al in the year 2004 which showed that malnutrition affects most the rural setting than the urban setting (6). This difference could be due to the problem of reporting since most health facilities don't effectively have trained personnel in the detection and management of malnourished children; as noted from the incomplete nature of some of the forwarded monthly reports.…”
Section: Discussion:-contrasting
confidence: 85%
“…On the other hand some rural health areas like Akok Maka and Mindourou showed very low or no case of malnutrition for the time duration of the study. The result of this study in terms of geographical distribution is in contrary to the research of Smith et al in the year 2004 which showed that malnutrition affects most the rural setting than the urban setting (6). This difference could be due to the problem of reporting since most health facilities don't effectively have trained personnel in the detection and management of malnourished children; as noted from the incomplete nature of some of the forwarded monthly reports.…”
Section: Discussion:-contrasting
confidence: 85%
“…En general, en la literatura se argumenta que el 谩mbito urbano posee mejores condiciones ambientales y sanitarias que el rural (Comisi贸n Econ贸mica para Am茅rica Latina y el Caribe [CEPAL], 2008;Smith, Ruel y Ndiaye, 2005). Sin embargo, estos planteos desestiman las grandes disparidades internas que pueden existir dentro de las ciudades, debidas principalmente a la desigual distribuci贸n de variables socioecon贸micas influyentes (CEPAL, 2008).…”
Section: Discussionunclassified
“…In modern developing countries, there is active debate about what defines "urbanness" (Dor茅lien et al 2013;Hugo et al 2003) and when and why urban advantages in infant and child health exist (Fink et al 2014;G眉nther and Harttgen 2012;Jankowska et al 2013;Montgomery and Hewett 2005;Smith et al 2005; Van de Poel et al 2007). Bocquier et al (2011) pointed out that urban advantages depend on the services and economic opportunities that a city provides, whereas Sastry (1996) noted that the effects of community-level variables on child health often depend on context-that is, that when exploring the effects of place on health, interactions are often important.…”
Section: Introductionmentioning
confidence: 99%